Răspuns :
6)
a+b=74
a=b+32
b+32+b=74
2b=74-32
2b=42
b=42:2
b=21
a+21=74
a=74-21
a=53
7)
a+b=68
a=3b
3b+b=68
4b=68
b=68:4
b=17
a+17=68
a=68-17
a=51
8)
a=4b
a-b=69
4b-b=69
3b=69
b=69:3
b=23
a=4x23=92
9)
a+b=97
b=a+1
a+a+1=97
2a=97-1
2a=96
a=96:2
a=48
b=48+1=49
a+b=74
a=b+32
b+32+b=74
2b=74-32
2b=42
b=42:2
b=21
a+21=74
a=74-21
a=53
7)
a+b=68
a=3b
3b+b=68
4b=68
b=68:4
b=17
a+17=68
a=68-17
a=51
8)
a=4b
a-b=69
4b-b=69
3b=69
b=69:3
b=23
a=4x23=92
9)
a+b=97
b=a+1
a+a+1=97
2a=97-1
2a=96
a=96:2
a=48
b=48+1=49